A new instrumentation system for training rowers - Hawkins, D. (Journal of Biomechanics, 2000)
A dry-land rowing system was developed to provide the coach and/or athlete with quantitative information about the athlete's kinetics and kinematics while the athlete trains. This system consists of a Concept II rowing ergometer instrumented with a force transducer and potentiometer, four electrogoniometers attached to the athlete's ankle, knee, hip, and elbow, and a data acquisition computer. The force transducer is used to quantify the athlete's pulling force. The potentiometer signal is used to locate the position of the handle. The electrogoniometers provide signals proportional to joint angles. A link segment model of the human body is used to locate joint centers based on limb lengths and joint angles. The computer is used to collect and process all the transducer signals, perform the link segment calculations and provide feedback to the coach or athlete in the form of a stick figure animation overlaid with kinematic and kinetic information. This system allows the coach and athlete to quickly study a rower's mechanics, to evaluate the effects that technique changes have on the power produced by the athlete, and to identify technique differences between athletes.